Exploring the Steady-State Relationship Between Credit and GDP for a Small Open Economy–The Case Of Ireland - Kelly, Robert; McQuinn, Kieran; Stuart, Rebecca (Economic & Social Studies, 2011)
The rapid increase in credit in an economy is now commonly perceived to be one of the leading indicators of financial instability. This view has been reinforced by the aftermath of the international financial crisis, which commenced in mid-2007. A key policy response has been to focus on the ratio of private sector credit to GDP for an economy, observing, in particular, significant deviations between the actual and long-run trends of the ratio. This paper examines the issue of the steady-state relationship between private sector credit and GDP in the case of Ireland, a country which, even by international standards, experienced a sizeable expansion in credit over the past 10 years.
Keywords: credit; GDP; Ireland